2020
DOI: 10.1186/s12879-020-05345-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal clusters of avian influenza a (H7N9) virus in humans across five epidemics in mainland China: an epidemiological study of laboratory-confirmed cases

Abstract: Background: Avian influenza A (H7N9) virus was first reported in mainland China in 2013, and alarming in 2016-17 due to the surge across a wide geographic area. Our study aimed to identify and explore the spatial and temporal variation across five epidemics to reinforce the epidemic prevention and control. Methods: We collected spatial and temporal information about all laboratory-confirmed human cases of A (H7N9) virus infection reported in mainland China covering 2013-17 from the open source. The autocorrela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this study, we observed similar results showing that high‐risk regions of human avian influenza mainly distributed in South China, with a trend of northwards shift to Central China. Previous studies have found that H7N9 had a trend of increase with obvious spatial expansion of outbreaks to the north of China (Martin et al, 2011; Shan et al, 2020). Our results showed that human avian influenza had a favorable condition of the main decisive factor Bio12 (annual precipitation) at a relatively high level of about 1168.28 mm.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we observed similar results showing that high‐risk regions of human avian influenza mainly distributed in South China, with a trend of northwards shift to Central China. Previous studies have found that H7N9 had a trend of increase with obvious spatial expansion of outbreaks to the north of China (Martin et al, 2011; Shan et al, 2020). Our results showed that human avian influenza had a favorable condition of the main decisive factor Bio12 (annual precipitation) at a relatively high level of about 1168.28 mm.…”
Section: Discussionmentioning
confidence: 93%